Renal X-inactivation in female individuals with X-linked Alport syndrome primarily determined by age - Günthner, Roman; Knipping, Lea; Jeruschke, Stefanie; Satanoskij, Robin; Lorenz-Depiereux, Bettina; Hemmer, Clara; Braunisch, Matthias C.; Riedhammer, Korbinian M.; Ćomić, Jasmina; Tönshoff, Burkhard; Tasic, Velibor; Abazi-Emini, Nora; et al. (Frontiers in Medicine, 2022)
X-linked Alport syndrome (AS) caused by hemizygous disease-causing variants in COL4A5 primarily affects males. Females with a heterozygous state show a diverse phenotypic spectrum ranging from microscopic hematuria to end-stage kidney disease and extrarenal manifestations. In other X-linked diseases, skewed X-inactivation leads to preferential silencing of one X-chromosome and thus can determine the phenotype in females. We aimed to show a correlation between X-inactivation in blood and urine-derived renal cells and clinical phenotype of females with a heterozygous disease-causing variant in COL4A5 compared to healthy controls. 56 females with a heterozygous disease-causing COL4A5 variant and a mean age of 31.6 ± 18.3 SD years were included in this study. 94% had hematuria, 62% proteinuria >200 mg/day, yet only 7% had decreased eGFR. Using human androgen receptor assay X-inactivation was examined in blood cells of all 56 individuals, in urine-derived cells of 27 of these individuals and in all healthy controls. X-inactivation did not correlate with age of first manifestation, proteinuria or eGFR neither in blood, nor in urine. The degree of X-inactivation showed a moderate association with age, especially in urine-derived cells of the patient cohort (rho=0.403, p=0.037). Determination of X-inactivation allelity revealed a shift of X-inactivation towards the COL4A5 variant bearing allele. This is the first study examining X-inactivation of urine-derived cells from female individuals with Alport syndrome. A correlation between phenotype and X-inactivation could not be observed suspecting other genetic modifiers shaping the phenotype in female individuals with AS. The association of X-inactivation with age in urine-derived cells suggests an escape-mechanism inactivating the COL4A5 variant carrying allele in female individuals with AS.